(3ELGRI aj QhGjI GdaGJMIs - (3eMeO GdeQGHW Hf eMeO Hf CHj HcQ GdQcGOjs ((3ecI GdecQeI s)
(3ChdgG (B:s
(3SeY GdTjN GdYdGeI SjOi eMeO GdeQGHW Hf SjOi eMeO HecI GdeTQaI s
(3BNQgG (B:s
(3hPcQ GdTjN ai ELGRJg ai QhGjI GdaGJMI hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs